'Candidatus Liberibacter asiaticus' Accumulates inside Endoplasmic Reticulum Associated Vacuoles in the Gut Cells of Diaphorina citri. Issue 1 (December 2017) - Ghanim, Murad; Achor, Diann; Ghosh, Saptarshi; Kontsedalov, Svetlana; Lebedev, Galina; Levy, Amit
Abstract Citrus greening disease known also as Huanglongbing (HLB) caused by the phloem-limited bacterium 'Candidatus Liberibacter asiaticus' (CLas) has resulted in tremendous losses and the death of millions of trees worldwide. CLas is transmitted by the Asian citrus psyllidDiaphorina citri . The closely-related bacteria 'Candidatus Liberibacter solanacearum' (CLso), associated with vegetative disorders in carrots, is transmitted by the carrot psyllidBactericera trigonica . A promising approach to prevent the transmission of these pathogens is to interfere with the vector-pathogen interactions, but our understanding of these processes is limited. It was recently reported that CLas induced changes in the nuclear architecture, and activated programmed cell death, inD .citri midgut cells. Here, we used electron and fluorescent microscopy and show that CLas induces the formation of endoplasmic reticulum (ER)-associated bodies. The bacterium recruits those ER structures into Liberibacter containing vacuoles (LCVs), in which bacterial cells seem to propagate. ER- associated LCV formation was unique to CLas, as we could not detect these bodies inB .trigonica infected with CLso. ER recruitment is hypothesized to generate a safe replicative body to escape cellular immune responses in the insect gut. Understanding the molecular interactions that undelay these responses will open new opportunities for controlling CLas.